Eksplorasi Identitas Diri dan Motivasi Belajar Siswa SMP di Masa Pubertas : 1. Konsep Dasar Identitas Diri Pada Masa Smp 2. Perubahan Motivasi Belajar pada Masa Pubertas 3. Implikasi Psikologis dan Pendidikan - TRI PURNAMA SARI; Ma`mun Hanif (Jurnal Inovasi Pendidikan dan Ilmu Sosial, 2026)
This study aims to understand the importance of self-identity exploration and learning motivation among junior high school students during puberty. Early adolescence is a transitional phase toward maturity marked by physical, emotional, and social changes. This research employs a qualitative descriptive approach using interviews, observations, and documentation techniques. The findings indicate that selfidentity formation is influenced by family, peers, social media, and the school environment. Meanwhile, students’ learning motivation tends to increase when they receive emotional support and possess strong self-efficacy. Teachers play a vital role as motivators and facilitators in helping students develop their potential and maintain emotional stability during the learning process.